Data about the proteins and aminoacid contained in some Black Sea molluscs - Mîrza, Maria (Cercetări Marine - Recherches Marines, 2026)
The paper presents data about the proteins and free and bound amino-acids found in Mytilus galloprovincialis, Mya arenaria and Rapana thomaslana. The proteins analysis has shown a higher content in Mytilus galloprovinicialis and Mya arenarla ( 2 and 56 p. c. of the dried substance ) and a lower one In Rapana thomasiana (46p.c. of the dried substance). Using the single-dimension paper chromatography technique for the separation of the amino-acids, one has identified 17 free and bound amino-acids: sulphur compounds, lysine, histidine, arginine, asparagine, serine + aspartic acid, glycocoll, glutamic acid, threonine, alpha-alanine , proline, tyrosine, tryptophan, methionine, valine, phenyl-alanine and leucine.